Valorization of postharvest waste from table grapes through the production of spirits and distillate by-products based on their antioxidant capacity - Fermín Humberto Arévalo-Ortiz; Juan Carlos Palma; Jacqueline Jannet Dioses-Morales; Amelia Devorah Arias-Durand; Gaby Espinoza-Córdova; Miki Gonzales-Uscamayta; Joel Claudio Rengifo-Maravi; Epifanio Teófilo Chire-Murillo; Víctor Caro Sánchez-Benites; Paola Jorge-Montalvo; Lizardo Visitación-Figueroa (Waste Management Bulletin)
The postharvest stage of table grapes generates waste that can be valorized. This research evaluated the valorization potential of Red Globe grape waste for the production of spirits and assessed the antioxidant capacity of their by-products (head, body, and tail of the distillate, and vinasse). The waste underwent alcoholic fermentation using Saccharomyces cerevisiae, followed by fractional distillation in a copper alembic still to separate the head, body (main spirit), and tail fractions, along with the resulting vinasse. The volatile compounds, total phenolic content (TPC), total flavonoid content (TFC), antioxidant capacity, and phenolic compounds were analyzed by UPLC-MS. The body fraction (distillate), containing 42 % (v/v) ethanol, could be classified as a spirit beverage. However, it exhibited higher levels of acetaldehyde, propanol, and acetic acid, suggesting the need for maturation. The head and tail fractions were suitable for rectification and use as industrial alcohol. Principal component analysis (PCA) indicated that antioxidant components were mainly concentrated in the vinasse, which exhibited notable antioxidant capacity values of 5.75 μmol TE/mL as Ferric reducing antioxidant power (FRAP) and 3.596 μmol TE/mL as DPPH, along with high TPC and TFC levels. Fourteen phenolic compounds were also identified, including kaempferol glycoside, epicatechin, and caftaric acid. This positions vinasse as a valuable source for the extraction of bioactive antioxidant compounds or as a potential functional beverage. Overall, the valorization of postharvest waste is a viable approach for producing spirit beverages while also highlighting the potential of by-products, particularly vinasse, as rich sources of antioxidants.